Malnourished Millions - Are We Doing Enough? - Apurva Ratnu; Hariprakash Hadial (Indian Association of Preventive and Social Medicine, 2022)
Nutrition word is derived from the Latin verb 'Nutrire" which means to nourish. Indian equivalent to nutrition is POSHAN. The development of a fertilized Ova cell into a full-grown human body consisting of trillions of cells is one of the finest miracles of nature on display and it is primarily dependent on adequate and appropriate nutrition.